(untitled) (International Seven Journal of Multidisciplinary, 2025)
The article in question anticipates the principles present in the National Common Curriculum Base (BNCC) by addressing the pedagogical value of toys and games in the context of early childhood education. Such elements are highlighted as essential tools for the cognitive development of children, functioning not only as recreational activities, but as true didactic and methodological instruments. Play is understood as a natural and privileged form of learning, through which children interact with the world, experience new possibilities, express their creativity and develop critical and social skills. When playing, the child symbolically elaborates reality, observes and imitates the behavior of adults, constructs meanings and advances in different stages of their physical, emotional, intellectual and social development. Playing is no longer just a playful moment and is now understood as a fundamental educational practice for the integral formation of the child.